Expressiveness is more Democratic than Originality. Fourteen Theses –Keneth Goldsmith Inspired for a Literature in the Digital Age - Rodríguez, Jaime Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper proposes a reading of American poet Keneth Goldsmith›s Uncreative Writing. ManagingLanguage in the Digital Age (2015) which corresponds to my personal review of the book –linked withother readings and particularly with my creative and research experience. It is organized by «theses» orpieces that briefly develop some of the ideas contained in Goldsmith›s proposal. This way of proceedinghas generated three approaches: 1) post-identity expressiveness as a substitute of creative authenticity,2) the literary canonical forms’ reevaluation as an effect of the deployment of interactive digital communication, 3) the effects on literary practice in the digital culture. With this reading of Goldsmith, a callon understanding the possibilities of the digital as an opportunity to renew literary practice is proposedat the end. The paper ends with an addendum: the short story “El hombre de la esquina”, which complements, in a fictional register, the ideas elaborated here.